Confiablidad de dos criterios de medición de la actividad electrográfica del músculo orbicular superior de los labios durante la deglución y la fonación - Gabriel Jaime Gallego-R; Luisa Fernanda Villegas-T (Universidad de Antioquia, 2003)
The diagnostic tools in Dentistry that includes sequential measurements present several problems concerning its reliability, due to the techniques and human factors. Among those variables, there are some static such as cephalometric, anthropometric or dental studies and some functional such as those that evaluate electrical and mechanical activity of the craniofacial muscles. Objective: the aim of the study was to evaluate the reliability of the measurement criteria of the Upper Orbicularis Oris muscle electromyographic activity registration (AEMG) during swallowing and phonation in two sessions separated by 8 days. Materials and Methods: 15 healthy subjects of both sex between 18 and 25 year old participated in the study. The swallowing and phonation were evaluated with superficial electromyography (EMG), three times a session with a resting time of 60 seconds between them in two different days separated by 8 days. Results: the obtained data presented in the study show a high reliability of the Upper Orbicularis Oris muscle during phonation and swallowing for the numerical integration and for the normalized RMS in the time as well.